2014
DOI: 10.1371/journal.pone.0110604
|View full text |Cite
|
Sign up to set email alerts
|

Arginase 2 Deficiency Prevents Oxidative Stress and Limits Hyperoxia-Induced Retinal Vascular Degeneration

Abstract: BackgroundHyperoxia exposure of premature infants causes obliteration of the immature retinal microvessels, leading to a condition of proliferative vitreoretinal neovascularization termed retinopathy of prematurity (ROP). Previous work has demonstrated that the hyperoxia-induced vascular injury is mediated by dysfunction of endothelial nitric oxide synthase resulting in peroxynitrite formation. This study was undertaken to determine the involvement of the ureahydrolase enzyme arginase in this pathology.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 48 publications
3
41
0
Order By: Relevance
“…On the other hand, although both ARG1 and ARG2 are present in endothelial cells, ARG2 predominates, and arginase inhibition stimulates NO through eNOS[32] as well as increasing urea production in endothelial tissue, suggesting that a decrease of ARG2 activity could have the same effect on nNOS in neurons. In fact, deletion of ARG2 causes mice to be more susceptible to brain injury from ischemic and excitotoxic challenges[33], though the same deletion is protective against retinal vascular degeneration[34], demonstrating that even ARG2/nNOS activity may be regionally diverse, or sensitive to regional Mn accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, although both ARG1 and ARG2 are present in endothelial cells, ARG2 predominates, and arginase inhibition stimulates NO through eNOS[32] as well as increasing urea production in endothelial tissue, suggesting that a decrease of ARG2 activity could have the same effect on nNOS in neurons. In fact, deletion of ARG2 causes mice to be more susceptible to brain injury from ischemic and excitotoxic challenges[33], though the same deletion is protective against retinal vascular degeneration[34], demonstrating that even ARG2/nNOS activity may be regionally diverse, or sensitive to regional Mn accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…While the role of NO in vascular injury is well discussed, involvement of arginase in the vascular injury has only recently been appreciated. Our laboratory has found that A2 plays a key role in the hyperoxia-mediated vascular injury through a mechanism involving superoxide and peroxynitrite formation [87]. Studies using A2 deficient mice in the OIR model showed significant decreases in vaso-obliteration compared to the wild type OIR retina, demonstrating involvement of A2 in OIR-induced vascular injury.…”
Section: Arginase and Cns Disease/injurymentioning
confidence: 99%
“…Pathological situations in which vascular contacts of horizontal cells play a role have been demonstrated in mice with oxygen-induced retinopathy, where links appear to exist between neurovascular cell injury and the arginase pathway (Suwanpradid et al, 2014). Beforehand, Ahuja et al (2005) aimed to clarify whether and how glutathione S transferase (GST) helps to protect photoreceptor cells.…”
Section: Horizontal Cellsmentioning
confidence: 99%